The UI/UX Design of a Mobile-Based Catering Application Using the Activity Centered Design Method - Faizal Rahmadani; Yeremia Alfa Susetyo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Catering services represent a practical option to meet individual food requirements. Having catering services available will help people find solutions for their food requirements more easily. The catering industry stands out as one of the most profitable business sectors. The support of this factor leads many individuals to choose catering services or to open their catering businesses. The process of placing catering orders by users and managing catering businesses by owners remains conventional. This study intends to establish UI UX elements for a mobile-based catering app through Activity Centered Design methodology. The Activity Centered Design method targets the specific activities performed by future users when they engage tasks. The product feasibility for potential users requires the execution of the Requirements stage followed by Design phase then Implementation phase and finally the Evaluation stage. The completed stages lead to the acquisition of feasibility testing results by measuring prospective users' satisfaction levels. The assessment of adjectives showed that the test achieved an 83.5 score which falls under the